Lead and disrupt how to solve the innovator's dilemma - O'Reilly, Charles A.; Tushman, Michael L. 1943- (Stanford Business Books, 2016)
Contents: Today's innovation puzzle -- Explore and exploit -- Achieving balance with innovation streams -- Six innovation stories -- Getting it right versus almost right -- What it takes to become ambidextrous -- Leaders (and their teams) as linchpins -- Leading change and strategic renewal